Catorce teoremas modales consistentes con la teoría de los modelos mentales - López-Astorga, Miguel (Prometeica - Revista de Filosofía y Ciencias, 2022)
Very important concepts in the theory of mental models are those of ‘possibility’ and ‘necessity’. Based on the definitions this psychology theory gives for those concepts, it has been shown that it complies with the requirement Fitting and Mendelsonh provides in general for modal logic. That requirement consists of being coherent with the modal interpretation of the square of opposition presented by Aristotle. This paper tries to move forward in this direction. It analyzes fourteen modal theorems indicated by Carnap under the approach of the theory of mental models. The results reveal that the theory is also compatible with those theorems.